Efektivitas Corporate Social Responsibility (CSR) Energy Equity Epic Sengkang Pty. Ltd - Herdi Syam (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The effectiveness of the Corporate Social Responsibility (CSR) program in Indonesia still needs to be improved. This can be seen from the number of companies that make CSR programs only a formality obligation without thinking about how much the benefits of the program are implemented for the community and the environment. This article discusses the effectiveness of Corporate Social Responsibility at Energy Equity Epic Sengkang Pty. Ltd. which is analyzed using indicators of goal achievement, integration and adaptation. The research method used is a qualitative approach with data collection techniques through literature review, observation and interviews, then analysis and data processing are carried out using reduction techniques and relevant data grouping. The results of the research are presented using descriptive techniques in the Corporate Social Responsibility Program at Energy Equity Epic Sengkang Pty. Ltd. implemented by first communicating, coordinating and socializing with the government and the community. The areas of CSR implementation are education, health, economy, public facilities and the environment. CSR programs implemented meet effectiveness indicators, namely goal achievement, integration and adaptation.